Pegomya disticha Griffiths and P. cedrica Huckett (Diptera: Anthomyiidae)—first documented case of insects trespassing the silica barrier of Common scouring-rush, Equisetum hyemale L. - Michelsen, Verner; Palmer, Michael W. (Zootaxa, 2020)
Scouring-rushes (Equisetum sg. Hippochaete) are a group of horsetails with perennial aerial shoots strongly encrusted in silica. Accordingly, they seem to resist attacks from most herbivorous insects. Michelsen (2008) speculated that larval development of the European Pegomya terminalis (Rondani) and related anthomyiids takes place in specific scouring-rushes. Presently, we document that the larvae of two North American species related to P. terminalis attack developing shoots of Common scouring-rush, Equisetum hyemale L. Both species, Pegomya disticha Griffiths and P. cedrica Huckett, were found to coexist in a population of scouring-rush in Oklahoma. Various aspects of the life-history and morphology (3rd instar larva, male and female adults) for both species are described and documented by photos.